Development and Acceptability of Mead Wine Flavored with Dragon Fruit (Selenicerius undatus) - Agcaoili, Josiefel Zamora (PLANTA TROPIKA, 2025)
This paper discusses the development and acceptability of Mead wine flavored with Dragon Fruit. A Quantitative Descriptive Analysis Survey was utilized among forty (40) panelists who are experts in alcohol while 75 respondents were randomly selected as participants in the sensory analysis using a Hedonic rating scale with a 5-point Likert scale. The results of the study have shown that the product was acceptable considering its color, aroma, taste and even the alcohol content of both treatments. In the findings, the highest responses on color is ruby with 62.5%, responses on aroma are regarded as sweet, tangy and even zesty nuance. The taste reveals that it is fairly acceptable with a 2.30 mean, which accounts for its acidity and good for food pairing. On the overall acceptability level of the three coded samples, wine coded control got the highest description of high acceptable and a mean of 4.38. While in the willingness to purchase the product, commercial product got the highest mean of 4.13, acceptable and wine with code treatment 1 got a high score of 4.03, also acceptable. The results of this study imply that mead with added dragon fruit has the potential to produce mead that is preferred by respondents.